An Integrated Pavement Maintenance Management Model for Coastal Roads under Seawater Exposure and Traffic Loading - Paikun Paikun; Daniel Arie Susanto; Lisa Oksri-Nelfia; Sri Wiwoho Mudjanarko; Basil David Daniel; Williams Dunu; Deshinta Arrova Dewi (Universitas Trisakti, 2026)
Aim: This study aims to develop an adaptive management and maintenance model for flexible pavement in coastal areas by integrating road condition evaluation, cost analysis, and the effects of seawater immersion. The model is intended to improve maintenance efficiency, extend pavement service life, and support sustainable infrastructure management. Methodology and results: A quantitative and experimental approach was employed. Field surveys assessed pavement conditions using the Pavement Condition Index (PCI), Surface Distress Index (SDI), and International Roughness Index (IRI). Asphalt samples were tested in the laboratory under seawater immersion to evaluate strength reduction through Marshall and Indirect Tensile Strength tests. Damage data were integrated with maintenance cost analysis and traffic volume, producing a predictive model using regression and correlation analysis. Initial results indicate that seawater immersion significantly accelerates pavement deterioration and increases maintenance costs compared to normal conditions. Conclusion, significance, and impact study: he proposed model provides a comprehensive framework by considering technical, economic, and environmental factors specific to coastal infrastructure. Findings highlight the importance of condition-based maintenance strategies that are adaptive to climate change and extreme environmental risks. This study contributes to achieving sustainable infrastructure, resilient cities, and climate action for coastal environments.